Investigation of Source Parameters of Roudbar-Manjil Earthquake Using Hybrid Simulation Method - Ali Hadian (Iranian Society of Structrual Engineering (ISSE), 2015)
For time history analysis of structures, appropriate records are needed. Due to the lack of strong-motion records from large earthquakes in some parts of Iran (e.g. Tehran region), earthquake simulation is a useful tool for studying strong-motion characteristics. In this study, a hybrid method has been used for obtaining source parameters of the 1990 Rudbar-Manjil earthquake (Mw7.3). In this simulation we assume fault plane, slip distribution and etc., then each parameter optimized after comparing simulated results with observed ones. In this hybrid method low frequency component of record obtained by the wave-number scheme that is a deterministic method and high frequency component obtained by the stochastic simulation method of Boore (2003), extended to the case of finite faults. Records from the stochastic method filtered with a high pass filter (fc=1.5 Hz) and results from the deterministic method filtered with low pass filter (fc=1.5 Hz), then the time-histories have been combined/added in the time domain. Final results have been compared with observed PSA and PSV in specified strong-motion stations. After comparing, optimized parameters have found, then based on this optimized parameters intensity contour has drawn; simulated intensity contours show good match with and observed ones. Best parameters are 2500 m/s for rupture velocity and 3 seconds for ramp function (i.e. rise time) and 36.82° N and 49.40° for earthquake epicenter. The results are important for the assessment of hazards in other seismically active parts of Alborz mountains (e.g. Greater Tehran area).